Studies on the Volatility and Tail Behaviour of Foreign Exchange Rates - Yeh, Wen-Wen (2010)
Based on GARCH, TGARCH, EGARCH models with three different distributional assumptions, we find that foreign exchange rates are better described by fat-tailed distributions in terms of goodness-of-fit. Moreover, the asymmetric effect parameter capturing the positive and negative shocks on volatility in the EGARCH model is statistically significant different from zero in all six currency pairs whereas that in the TGARCH model are mostly insignificant. Further, the tail estimate for EURUSD with different frequencies is stable, and the shape parameter for some currency pairs is relatively stable under the certain condition. The shape parameter of minima for the EURUSD return might indicate less possibility of extremal movement while AUDUSD is the opposite.